An American Provence - Huber, Thomas Patrick (University Press of Colorado, 2011)
"I have talked about luscious wines and succulent fruit and exquisite dinners. But there may be no more evocative experience of the two valleys than the smell of new-mown hay in the fields at dusk. If a person were to close their eyes, they could not tell if they were in Provence or the North Fork Valley. That sweet, earthy odor is part of the beauty of these places."--An American Provence In this poetic personal narrative, Thomas P. Huber reflects on two seemingly unrelated places-the North Fork Valley in western Colorado and the Coulon River Valley in Provence, France-and finds a shared landscape and sense of place. What began as a simple comparison of two like places in distant locations turned into a more complex, interesting, and personal task. Much is similar-the light, the valleys, the climate, the agriculture. And much is less so-the history, the geology, the physical makeup of villages. Using a geographer's eye and passion for the land and people, Huber examines the regions' similarities and differences to explore the common emotional impact of each region. Part intimate travelogue and part case study of geography in the real world, An American Provence illuminates the importance sense of place plays in who we are.
Keywords: Landscape assessment -- France -- Coulon River Region.; Landscape assessment -- Colorado -- Gunnison River Valley.; Landscape assessment -- Colorado -- Paonia Reservoir.; Geographical perception -- France -- Coulon River Region.; Geographical perception -- Colorado -- Gunnison River Valley.; Geographical perception -- Colorado -- Paonia Reservoir.; Coulon River Region (France) -- Geography.; Paonia Reservoir (Colo.) -- Geography.; Gunnison River Valley (Colo.) -- Geography.; SCIENCE -- Earth Sciences -- General.; SCIENCE -- Earth Sciences -- Geography.; Geographical perception; Geography; Landscape assessment; Colorado -- Gunnison River Valley; Colorado -- Paonia Reservoir